Efficacy of Jiedu Pingsou Decoction Combined with Azithromycin in the Treatment of Children with Mycoplasma Pneumonia and Its Effects on Inflammatory Factors and Immune Function. (24th March 2022) - Lin, Shaoli; Wang, Shiyun; Zhang, Juan; Zhuang, Min; Meng, Zhen; Liu, Jianhua
Abstract : Objective . The purpose of this study is to detect the clinical efficacy of Jiedu Pingsou Decoction combined with azithromycin in the treatment of children with mycoplasma pneumonia and the effect on inflammatory factors and immune function in children. Methods A total of 68 children with mycoplasma pneumonia in our hospital from January 2021 to January 2022 were included in this study, and they were randomly divided into the control group and the observation group with 34 cases in each group. The children in the control group were treated with azithromycin, and the children in the observation group were treated with Jiedu Pingsou Decoction on this basis. The clinical manifestations, treatment effects, blood routine, serum inflammatory factor levels, and T cell subsets before and after treatment were compared between the two groups. Results The total effective rate in the observation group was 94.12%, which was higher than that in the control group, which was 82.35%, and the difference between the two groups was statistically significant ( P < 0.05). After treatment, the levels of CD3+, CD4+, and CD4+/CD8+ in the two groups were higher than those before treatment, and the level of CD8+ was lower than before treatment. The difference between groups was statistically significant ( P < 0.05). The levels of serum C-reactive protein (CRP), tumor necrosis factor- α (TNF- α ), interferon gamma (IFN- γ ), interleukin-6 (IL-6), and interleukin-10 (IL-10) in the two groups after treatment were lower than those before treatment, and the difference between the two groups was statistically significant ( P < 0.05). The difference between groups was statistically significant ( P < 0.05). There were 4 cases and 2 cases of adverse reactions in the control group and the observation group, respectively, and the difference between the two groups was statistically significant ( P > 0.05). Conclusion Jiedu Pingsou Decoction combined with azithromycin can effectively improve the levels of T cell subsets, immune function, and inflammatory factors in children with mycoplasma pneumonia, improve clinical symptoms, and is safe and stable, and can be used in clinical practice.